The R0 and R1 Properties in Fuzzy Soft Topological Spaces - Salem Al-wosabi (s. Saleh); Amani Salemi (Journal of New Theory)
The purpose of this paper is to introduce and study some new properties so-calledfuzzy soft Ri (for short, FSRi, i = 0, 1) on fuzzy soft spaces by using quasi-coincident relation forfuzzy soft points, we get some characterizations and properties of them. Also, the relationships ofthese properties in fuzzy soft topologies which are constructed from crisp topology and soft topologyover X and vice versa are studied with some illustrative examples.